PERLINDUNGAN HUKUM NOTARIS ATAS PENGAMBILAN AKTA OLEH PENYIDIK DALAM KUHAP BARU - Maitsa, Rania Nisrina Muna; Silviana, Ana (Sebelas Maret University, 2026)
Notaries, as public officials, are vested with the authority to draw up authentic deeds and therefore cannot be treated as ordinary legal subjects in the criminal investigation process. Legal protection for notaries has been normatively regulated in Article 66 of the Notary Law, which requires the approval of the Notary Honorary Council for the retrieval of deeds and the summoning of notaries by investigators. The new Indonesian Criminal Procedure Code (KUHAP) has come into force and introduces provisions stipulating that investigators are not authorized to directly request or seize notarial deeds, but must obtain prior permission from the Head of the District Court. This condition raises issues regarding the harmonization of regulations between the new KUHAP and Article 66 of the Notary Law in providing legal protection for notaries. This study aims to analyze the legal protection framework for notaries against the retrieval of deeds and summons by investigators from the perspective of the new KUHAP, as well as to assess its conformity with the procedures stipulated in Article 66 of the Notary Law. The research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that although the new KUHAP strengthens legal protection for notaries through a court authorization mechanism, there is still no explicit regulation integrating this mechanism with the approval of the Notary Honorary Council. Therefore, regulatory harmonization is necessary to ensure legal certainty, the protection of notarial professional secrecy, and the effectiveness of the investigation process.